Aspek Hukum Dan Kelembagaan Dalam Peningkatan Efisiensi Dan Efektivitas Pengelolaan Wilayah Pesisir - Gatot Dwi Hendro Wibowo (Fakultas Hukum Universitas Islam Indonesia, 2009)
This research is intended to identify about the regulation and institution related to management of coastal area. Regarding the subject matter of this study, this research is a normative legal research. It employed several approach, i.e. conceptual approach and statutory approach. From this research, find out that (1) the authority of coastal area management can be find in sectoral regulation as such as tourism, environmental, land, mining, forestry regulation, etc. It consequence that many institution will be take about the coastal authority, (2) From the Institutional of view, the activities of cross sectoral, overlapping and potentialy conflict of authority, all of this, need the instotutional system with integration and coordination priority (3) The institutional approach by clear authority, strong institution and good procedure, can be increase efectively management of sustainable coastal area.